The Principles of Islamic Business Ethics in the Viral Success of Donat Kampar Galesong: A Review of Islamic Economic Law - Yusuf, Hardyansyah; Zubair, Muhammad Kamal; Aminah, St; Mahsyar, Mahsyar; Soi, Andi Bahri (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze the implementation of Islamic business ethics principles in the business activities of Donat Kampar Galesong, a growing local brand. The research employs a qualitative descriptive method with a phenomenological approach, focusing on firsthand experiences and perspectives of Donat Kampar Galesong employees. Islamic business ethics principles in this study are classified into three main variables: management ethics, marketing ethics, and environmental ethics. The findings indicate a high level of adherence to these principles, with implementation scores reaching 94.84% for management ethics, 96.48% for marketing ethics, and 95.89% for environmental ethics, leading to an overall average of 95.74%. These results confirm that Donat Kampar Galesong has successfully integrated Islamic business ethics into its operations, demonstrating a strong commitment to the values of justice (al-‘adl), transparency (al-shafafiyyah), and trustworthiness (al-amanah) within the framework of Sharia Economic Law. The study highlights how ethical business practices align with Islamic principles and contribute to sustainable business success. This study guides businesses to apply Islamic ethics, ensuring sustainability and promoting economic justice and social welfare.Keywords: Islamic Business Ethics; Environmental Ethics; Management Ethics; Marketing Ethics, Sharia Economic Law